Proceedings of the 23rd International Conference on Software Engineering. ICSE 2001
DOI: 10.1109/icse.2001.919102
|View full text |Cite
|
Sign up to set email alerts
|

Comparing frameworks and layered refinement

Abstract: Object-oriented frameworks are a popular mechanism for building and evolving large applications and software product lines. This paper describes an alternative approach to software construction, Java Layers (JL), and evaluates JL and frameworks in terms of flexibility, ease of use, and support for evolution. Our experiment compares Schmidt's ACE framework against a set of ACE design patterns that have been implemented in JL. We show how problems of framework evolution and overfeaturing can be avoided using JL'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…Some of the software engineering advantages of using mixins to build software layers (e.g., heap layers) have been discussed previously, especially focusing on ease of refinement [5,9,21]. We found that using heap layers as a means of stepwise refinement greatly simplified allocator construction.…”
Section: Software Engineering Benefitsmentioning
confidence: 81%
“…Some of the software engineering advantages of using mixins to build software layers (e.g., heap layers) have been discussed previously, especially focusing on ease of refinement [5,9,21]. We found that using heap layers as a means of stepwise refinement greatly simplified allocator construction.…”
Section: Software Engineering Benefitsmentioning
confidence: 81%
“…Eisenecker et al utilize static C++ metaprogramming [13]. Several approaches solve the extensibility problem, introduced by Findler et al [14]: Java Layers [8], Jak [5], Jiazzi [23]. Regarding the constructor problem and extensibility problem, FeatureC++ is inspired by these approaches.…”
Section: Related Workmentioning
confidence: 99%
“…One appropriate way to implement features of program families in a modular way are Mixin Layers [31]. Mixin Layers can be implemented using C++ templates [31], P++ [29], Jak [5], Java Layers [8], Jiazzi [23], and Delegation Layers [25]. All these approaches leave aside the problem of lacking crosscutting modularity.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixin layers [22] improve on this by using a layer of mixins to modularize a collaboration between many objects. Java Layers [4,3] adds mixin layers to the Java language. The sibling class pattern [3] enabled by Java Layers provides the same functionality as Jiazzi's open packages.…”
Section: Related Workmentioning
confidence: 99%